Localization-based imaging of malarial antigens during red cell entry reaffirms role for AMA1 but not MTRAP in invasion - Riglar,DT; Whitehead,L; Cowman,AF; Rogers,KL; Baum,J (Journal of Cell Science, 2016)
Microscopy-based localisation of proteins during malaria parasite invasion of the erythrocyte is widely used for tentative assignment of protein function. To date, however, imaging has been limited by the rarity of invasion events and poor resolution available, given micron size of the parasite, which leads to a lack of quantitative measures for definitive localisation. Here, using computational image analysis we have attempted to assign relative protein localisation during invasion using wide-field deconvolution microscopy. By incorporating three-dimensional information we present a detailed assessment of known parasite effectors predicted to function during entry but as yet untested or for which data is equivocal. Our method, longitudinal intensity profiling, resolves confusion surrounding localisation of apical membrane antigen (AMA1) at the merozoite-erythrocyte junction and predicts that the merozoite thrombospondin related anonymous protein (MTRAP) is unlikely to play a direct role in the mechanics of entry, an observation supported with additional biochemical evidence. This approach sets a benchmark for imaging of complex micron-scale events and cautions against simplistic interpretations of small numbers of representative images for assignment of protein function or prioritisation of candidates as therapeutic targets.